Bis-Amiridines as Acetylcholinesterase and Butyrylcholinesterase Inhibitors: N-Functionalization Determines the Multitarget Anti-Alzheimer's Activity Profile - Makhaeva, Galina F; Kovaleva, Nadezhda V; Boltneva, Natalia P; Rudakova, Elena V; Lushchekina, Sofya V; Astakhova, Tatiana Yu; Serkov, Igor V; Proshin, Alexey N; Radchenko, Eugene V; Palyulin, Vladimir A; Korabecny, Jan; Soukup, Ondrej; et al. (Molecules (Basel, Switzerland), 2022)
Using two ways of functionalizing amiridine-acylation with chloroacetic acid chloride and reaction with thiophosgene-we have synthesized new homobivalent bis-amiridines joined by two different spacers-bis-N-acyl-alkylene (3) and bis-N-thiourea-alkylene (5) -as potential multifunctional agents for the treatment of Alzheimer's disease (AD). All compounds exhibited high inhibitory activity against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) with selectivity for BChE. These new agents displayed negligible carboxylesterase inhibition, suggesting a probable lack of untoward drug-drug interactions arising from hydrolytic biotransformation. Compounds 3 with bis-N-acyl-alkylene spacers were more potent inhibitors of both cholinesterases compared to compounds 5 and the parent amiridine. The lead compounds 3a-c exhibited an IC50(AChE) = 2.9-1.4 µM, IC50(BChE) = 0.13-0.067 µM, and 14-18% propidium displacement at 20 μM. Kinetic studies of compounds 3a and 5d indicated mixed-type reversible inhibition. Molecular docking revealed favorable poses in both catalytic and peripheral AChE sites. Propidium displacement from the peripheral site by the hybrids suggests their potential to hinder AChE-assisted Aβ42 aggregation. Conjugates 3 had no effect on Aβ42 self-aggregation, whereas compounds 5c-e (m = 4, 5, 6) showed mild (13-17%) inhibition. The greatest difference between conjugates 3 and 5 was their antioxidant activity. Bis-amiridines 3 with N-acylalkylene spacers were nearly inactive in ABTS and FRAP tests, whereas compounds 5 with thiourea in the spacers demonstrated high antioxidant activity, especially in the ABTS test (TEAC = 1.2-2.1), in agreement with their significantly lower HOMO-LUMO gap values. Calculated ADMET parameters for all conjugates predicted favorable blood-brain barrier permeability and intestinal absorption, as well as a low propensity for cardiac toxicity. Thus, it was possible to obtain amiridine derivatives whose potencies against AChE and BChE equaled (5) or exceeded (3) that of the parent compound, amiridine. Overall, based on their expanded and balanced pharmacological profiles, conjugates 5c-e appear promising for future optimization and development as multitarget anti-AD agents.
Keywords: GPI-Linked Proteins; Cholinesterase Inhibitors; antioxidancia; GPI-vázané proteiny; aminochinoliny; neuroprotektivní látky; Structure-Activity Relationship; molekulární struktura; Molecular Structure; Alzheimerova nemoc; Alzheimer Disease; N-acylamide; β-amyloid (Aβ42); Neuroprotective Agents; amiridine; Molecular Docking Simulation; butyrylcholinesterase (BChE); acetylcholinesterasa; ADMET; molekulární modely; vztahy mezi strukturou a aktivitou; neuroprotection; simulace molekulového dockingu; Models, Molecular; kinetika; lidé; Antioxidants; Humans; Butyrylcholinesterase; Aminoquinolines; thiourea; Alzheimer’s disease (AD); acetylcholinesterase (AChE); butyrylcholinesterasa; Acetylcholinesterase; cholinesterasové inhibitory; antioxidants; Kinetics